Atmospheric and Ocean Dynamics May Explain Cycles in Oceanic Oscillations - Knut L. Seip; Øyvind Grøn (Climate, 2019)
What causes cycles in oceanic oscillations, and is there a change in the characteristics of oscillations in around 1950? Characteristics of oceanic cycles and their sources are important for climate predictability. We here compare cycles generated in a simple model with observed oceanic cycles in the great oceans: The North Atlantic Oscillation (NAO), El Niño, the Southern Oscillation Index (SOI), and the Pacific Decadal Oscillation (PDO). In the model, we let a stochastic movement in one oceanic oscillation cause a similar but lagging movement in another oceanic oscillation. The two interacting oscillations show distinct cycle lengths depending upon how strongly one oscillation creates lagging cycles in the other. The model and observations both show cycles around two to six, 13 to 16, 22 to 23, and 31 to 32 years. The ultimate cause for the distinct cycles is atmospheric and oceanic “bridges” that connect the ocean basins, but the distinct pattern in cycle lengths is determined by properties of statistical distributions. We found no differences in the leading or lagging strength between well separated basins (the North Atlantic and the Pacific) and overlapping ocean basins (both in the Pacific). The cyclic pattern before 1950 appears to be different from the cyclic pattern after 1950.